2019
DOI: 10.1038/s41467-019-11017-y
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting a heterotic gene through GradedPool-Seq mapping informs a rice-improvement strategy

Abstract: Hybrid rice breeding for exploiting hybrid vigor, heterosis, has greatly increased grain yield. However, the heterosis-related genes associated with rice grain production remain largely unknown, partly because comprehensive mapping of heterosis-related traits is still labor-intensive and time-consuming. Here, we present a quantitative trait locus (QTL) mapping method, GradedPool-Seq, for rapidly mapping QTLs by whole-genome sequencing of graded-pool samples from F 2 progeny via bulked-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
69
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(73 citation statements)
references
References 61 publications
4
69
0
Order By: Relevance
“…And previous studies indicated that OsMADS1 regulates spikelet development partly by specification of the lemma and palea and acts as an inhibitor of overdevelopment of the lemma and palea (Jeon et al 2000 ; Prasad et al 2001 ; Chen et al 2006 ; Wang et al 2017 ). Furthermore, recent studies indicated that OsMADS1 not only regulates spikelet development, but also plays important roles in regulating grain shape (Liu et al 2018 ; Sun et al 2018 ; Yu et al 2018 ; Wang et al 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…And previous studies indicated that OsMADS1 regulates spikelet development partly by specification of the lemma and palea and acts as an inhibitor of overdevelopment of the lemma and palea (Jeon et al 2000 ; Prasad et al 2001 ; Chen et al 2006 ; Wang et al 2017 ). Furthermore, recent studies indicated that OsMADS1 not only regulates spikelet development, but also plays important roles in regulating grain shape (Liu et al 2018 ; Sun et al 2018 ; Yu et al 2018 ; Wang et al 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…In previous years, many important genes or QTLs associated with heterosis have been identi ed in many species, such as WUSCHEL (WUS), (AUXIN-REGULATED GENE INVOLVED IN ORGAN SIZE) ARGOS in Arabidopsis [39], SINGLE FLOWER TRUSS (SFT) and fw2.2 in tomato [40,41], GW3p6 (OsMADS1), OsNramp5 (Natural Resistance-Associated Macrophage Protein 5), Ghd8/DTH8, Gn1a (OsCKX2), IPA1 (OsSPL14), Hd3a (Heading date3a) in rice [42][43][44][45] and CNR in maize [46]. These genes involved in various functions including cell number or cell cycle regulation; environmental adaption; heading date, plant height and grain-yield controlling.…”
Section: Discussionmentioning
confidence: 99%
“…1). RapMap has several notable advantages compared with traditional schemes of linkage and GWAS analysis, and recently reported methods for mapping and cloning functional genes (QTL-seq, QTGseq, MutMap and others) 31,[46][47][48] . (1) F 2 gradient populations constructed from trait-adjacent parents from diverse germplasms are technically central and innovative in RapMap (Fig.…”
Section: Discussionmentioning
confidence: 99%